The effectiveness of eucalyptus globulus and thymus vulgaris in reducing COVID-19 symptoms among COVID-19 patients at Al- Nasiriya City - Rawaa Kamel Abd; Duaa Abd Al Azem; Ayad Abbas Aend; Khalied Yassen Zakair (Journal of the Pakistan Medical Association, 2023)
Objective: To determine how Thymus vulgaris and Ecalyptus globulus affected the symptoms of coronavirus disease- 2019 patients. Method: The experimental case-control study was conducted in Al-Nasiriya city, Iraq, from December 15, 2020, to February 20, 2021, and comprised patients of either gender aged 20-50 years diagnosed with coronavirus disease- 2019 infection. The patients’ symptoms ranged from mild to severe. Half of the sample was exposed to the study’s treatment protocol, while the other half acted as control. Thyme, orange and lemon were employed as sources of vitamin C, as well as eucalyptus leaves and oil. The cases were exposed to eucalyptus vapours for 5-10 minutes after thoroughly washing the plant leaves (7-10 leaves or 5 drops of oil) and boiling them in drinking water at 100°C for 10- 15 minutes. Data was analysed using SPSS 23. Results: Of the 48 patients, 24(50%) were in each of the two groups. Age and gender were not significantly different (p>0.05), while body mass index and blood group distribution was significantly different between the groups (p<0.05). Overall, 22(45.8%) subjects had mild symptoms, 20(41.7%) had moderate symptoms and 6(12.5%) had severe symptoms. The improvement in the symptoms among the cases was significantly more than the controls (p<0.05) except nasal congestion (p>0.05). Conclusion: Using eucalyptus vapours in the form of dried leaves or oil could significantly lessen coronavirus disease- 2019 symptoms. Keywords: Eucalyptus, Thymus, Plant, Citrus, Cough, Smell, COVID-19, Leaves, Vaccines, Vitamins.